Efficient production of astaxanthin in Yarrowia lipolytica through metabolic and enzyme engineering - Abdullah, Chalak Najat; Liu, Mengsu; Chen, Qihang; Gao, Song; Zhang, Changtai; Liu, Shike; Zhou, Jingwen (Synthetic and systems biotechnology, 2025)
Astaxanthin is a natural red carotenoid, commonly used as an additive in the pharmaceutical industry and as a nutritional supplement owing to its notable antioxidant benefits. However, a complex biosynthetic pathway poses a challenge to de novo biosynthesis of astaxanthin. Here, Yarrowia lipolytica was engineered through multiple strategies for high level production of astaxanthin using a cheap mineral medium. For the production of β-carotene, a platform strain was constructed in which 411.7 mg/L of β-carotene was produced at a shake-flask level. Integration of algal β-carotene ketolase and β-carotene hydroxylase led to the production of 12.3 mg/L of astaxanthin. Furthermore, construction of HpBKT and HpCrtZ as a single enzyme complex along with the enhanced catalytic activity of the enzymes led to the accumulation of 41.0 mg/L of astaxanthin. Iterative gene integration into the genome and direction of the astaxanthin production pathway into sub-organelles substantially increased astaxanthin production (172.1 mg/L). Finally, restoration of the auxotrophic markers and medium optimization further improved astaxanthin production to 237.3 mg/L. The aforementioned approaches were employed in fed-batch fermentation to produce 2820 mg/L of astaxanthin (229-fold improvement regarding the starter strain), with an average productivity of 434 mg/L/d and a yield of 5.6 mg/g glucose, which is the highest reported productivity in Y. lipolytica. [Display omitted]